Characterization of encapsulated graphene layers using extreme ultraviolet coherence tomography - Wiesner, Felix; Skruszewicz, Slawomir; Roedel, Christian; Abel, Johann Jakob; Reinhard, Julius; Wuensche, Martin; Nathanael, Jan; Gruenewald, Marco; Huebner, Uwe; Paulus, Gerhard G.; Fuchs, Silvio (Optics Express, 2022)
Many applications of two-dimensional materials such as graphene require the encapsulation in bulk material. While a variety of methods exist for the structural and functional characterization of uncovered 2D materials, there is a need for methods that image encapsulated 2D materials as well as the surrounding matter. In this work, we use extreme ultraviolet coherence tomography to image graphene flakes buried beneath 200 nm of silicon. We show that we can identify mono-, bi-, and trilayers of graphene and quantify the thickness of the silicon bulk on top by measuring the depth-resolved reflectivity. Furthermore, we estimate the quality of the graphene interface by incorporating a model that includes the interface roughness. These results are verified by atomic force microscopy and prove that extreme ultraviolet coherence tomography is a suitable tool for imaging 2D materials embedded in bulk materials.
CRIS-Team Scopus Importer:2023-04-20